FINANCIAL TECHNOLOGY SEBAGAI INSTRUMEN INKLUSI KEUANGAN MENUJU BISNIS BERKELANJUTAN DI ERA VUCA - Triyas Nur Hayati (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2022)
The current business era is experiencing massive changes due to the uncertainty of industry fluctuations and tight competition, making businesses enter the VUCA era. This makes business activists required to adapt to circumstances that are prone to change (Volatility), the uncertainty of circumstances (Uncertainty), circumstances full of complexity (Complexity), and floating circumstances (Ambiguity). Therefore, innovation is needed so that business actors remain active in facing the challenges of the VUCA era. Digital transformation brings many changes in the industrial world. Financial Technology has the potential to play a role in increasing financial inclusion and Business Sustainability. This study aims to systematically highlight the business model of financial technology from the relevant literature. The methodology used in this research is the study of literature. The results showed that the existence of Financial Technology has a positive impact on efforts to increase financial inclusion and Business Sustainability in the VUCA Era, which can be seen from the projected growth of Financial Technology, which has increased significantly. This research is expected to provide a view of the business world in observing the adoption of Financial Technology.